Pengaruh Profitabilitas, Struktur Aset dan Pertumbuhan Penjualan Terhadap Struktur Modal Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020 - Sukiranto; Rays, Muh (JOURNAL INTELEKTUAL, 2023)
Introduction/Main Objectives: To find out how profitability, asset structure and sales growth affect the capital structure of mining companies listed on the Indonesia Stock Exchange in 2017-2020. Background Problems: The net profit of coal mining in 2019 has fallen drastically, some have even reached more than 100 percent. Novelty: Re-testing in different industries and different testing periods. Research Methods: Using secondary data from the Indonesia Stock Exchange with the sample selection method using purposive sampling, in order to obtain a sample of 30 mining companies listed on the Indonesia Stock Exchange in 2017-2020 Finding/Results: That profitability has a significant negative effect on capital structure, asset structure has no significant effect on capital structure, and sales growth has no significant positive effect on capital structure. Conclusion: The capital structure policy first pays attention to the variables of profitability, asset structure and sales growth in order to be able to decide on the size of the appropriate capital structure so as to produce an optimal capital structure policy for the company.